2019
DOI: 10.1088/1742-6596/1380/1/012087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrogen peroxide on 304 stainless steel in high temperature water

Abstract: Hydrogen peroxide (H2O2), an oxidizer produced by water radiolysis, is considered one of the main contributors to corrosion of the stainless steel (SS) components in the cooling system of nuclear reactors. The detailed understanding of this chemical system is however still missing. The present research aimed to study the effects of H2O2 on 304 SS. The surface morphology and the chemical composition of the SS specimens after experiment were examined using Scanning Electron Microscope – Energy Dispersive X-ray (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The breakdown of Fe 2 O 3 with H 2 O 2 might explain the decreased corrosion resistance. [ 20 ] Makjan et al [ 21 ] showed that after the immersion of stainless steel in H 2 O 2 solutions, the amount of Cr ions in the solution was insignificant compared to that of Fe ions. Thus, the stability of the Cr‐rich layer could prevent a decrease in E pit .…”
Section: Discussionmentioning
confidence: 99%
“…The breakdown of Fe 2 O 3 with H 2 O 2 might explain the decreased corrosion resistance. [ 20 ] Makjan et al [ 21 ] showed that after the immersion of stainless steel in H 2 O 2 solutions, the amount of Cr ions in the solution was insignificant compared to that of Fe ions. Thus, the stability of the Cr‐rich layer could prevent a decrease in E pit .…”
Section: Discussionmentioning
confidence: 99%
“…This implies that oxidation can indeed occur [8,23,24]. The chemical paths of this process strongly depend on the composition and structu of the steel [25,26] and the product layer that forms on the surfaces. In general, corrosi also produces soluble metallic species and, in the presence of chloride anions, the fin product is the soluble Fe(III) chloride.…”
Section: General Frameworkmentioning
confidence: 99%
“…Figure 3 shows the mass variation of these alloys, ΔP %, expressed as (P0 − Pt)/P 100 (P0 and Pt being the initial weight and the weight of the metals at the moment t), a function of time, for samples kept for different times at 70 °C under the action of a soluti The chemical paths of this process strongly depend on the composition and structure of the steel [25,26] and the product layer that forms on the surfaces. In general, corrosion also produces soluble metallic species and, in the presence of chloride anions, the final product is the soluble Fe(III) chloride.…”
Section: Corrosion Experimentsmentioning
confidence: 99%